2004
DOI: 10.5194/angeo-22-889-2004
|View full text |Cite
|
Sign up to set email alerts
|

Observations of diverging field-aligned ion flow with the ESR

Abstract: Abstract. We report on observations of a diverging ion flow along the geomagnetic field that is often seen at the EISCAT Svalbard radar. The flow is upward above the peak of the electron density in the F-region and downward below the peak. We estimate that in such events mass transport along the field line is important for the ionization balance, and that the shape of the F-layer and its ion composition should be strongly influenced by it. Diverging flow typically occurs when there are signatures of direct ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…The resulting vertical pressure gradients would generate ion diffusion upward above the heating layer and downward below it. Statistical observations from the EISCAT Svalbard Radar lend some support to this interpretation (Buchert et al, ). However, ion downflow velocities due to pressure gradients are usually small (<1 km/s) (Buchert et al, ; Endo et al, ) compared to over 2–3 km/s in our study.…”
Section: Discussionmentioning
confidence: 92%
“…The resulting vertical pressure gradients would generate ion diffusion upward above the heating layer and downward below it. Statistical observations from the EISCAT Svalbard Radar lend some support to this interpretation (Buchert et al, ). However, ion downflow velocities due to pressure gradients are usually small (<1 km/s) (Buchert et al, ; Endo et al, ) compared to over 2–3 km/s in our study.…”
Section: Discussionmentioning
confidence: 92%
“…For identifying occurrence of ionospheric ion upflow, several criteria for selecting ion upflow events have previously been adopted [e.g., Endo et al , 2000; Buchert et al , 2004; Ogawa et al , 2009]. In the topside ionosphere, the signal‐to‐noise ratio becomes low, and sometimes the fits of incoherent scatter (IS) spectra converged to unrealistically high velocities.…”
Section: Instruments and Datamentioning
confidence: 99%
“…In general, it is useful to separate the problem into successive steps. The first step is the initial acceleration of bulk ion upflow events driven by ion heating and ambipolar diffusion as observed by incoherent scatter radars (ISRs) [ Wahlund et al ., ; Ogawa et al ., , , ; Buchert et al ., ; Skjæveland et al ., ], sounding rockets [ Arnoldy et al ., ; Lynch et al ., ; Frederick‐Frost et al ., ], and satellites in polar low Earth orbit in the F region ionosphere [ Coley et al ., ; Ogawa et al ., ; Lühr et al ., ; Chaston et al ., ; Lorentzen et al ., ; Sadler et al ., ]. The second step is that upflow events that have reached sufficiently high altitudes are exposed to wave energies available in the topside ionosphere/magnetosphere which drive nonthermal transverse acceleration of oxygen [ André and Yau , ; Strangeway et al ., ; Chaston et al ., ; Jacobsen and Moen , ].…”
Section: Introductionmentioning
confidence: 99%
“…Statistical work by Buchert et al . [] and Ogawa et al . [] showed that ion upflows above the European Incoherent Scatter Svalbard Radar (ESR) occurred for any magnetic local time (MLT) and Kp , but were most common around magnetic noon, with the peak at 13 MLT (upflow occurrence rate 18%) and somewhat more upflows prenoon (8–10%) than postnoon (5–10%, with a clear minimum around 18–20 MLT).…”
Section: Introductionmentioning
confidence: 99%